Common Variable Immunodeficiency and Neurodevelopmental Delay Due to a 13Mb Deletion on Chromosome 4 Including the NFKB1 Gene: A Case Report - Franco-Jarava, Clara; Valenzuela, Irene; Riviere, Jacques G.; Garcia-Prat, Marina; Martínez-Gallo, Mónica; Dieli-Crimi, Romina; Castells, Neus; Batlle-Masó, Laura; Soler-Palacin, Pere; Colobran, Roger (Frontiers in Immunology, 2022)
Syndromic immunodeficiencies are a heterogeneous group of inborn errors of immunity that can affect the development of non-immune organs and systems. The genetic basis of these immunodeficiencies is highly diverse, ranging from monogenic defects to large chromosomal aberrations. Antibody deficiency is the most prevalent immunological abnormality in patients with syndromic immunodeficiencies caused by chromosomal rearrangements, and usually manifests as a common variable immunodeficiency (CVID)-like phenotype. Here we describe a patient with a complex phenotype, including neurodevelopmental delay, dysmorphic features, malformations, and CVID (hypogammaglobulinemia, reduced pre-switch and switch memory B cells, and impaired vaccine response). Microarray-based comparative genomic hybridization (aCGH) revealed a 13-Mb deletion on chromosome 4q22.2-q24 involving 53 genes, some of which were related to the developmental manifestations in our patient. Although initially none of the affected genes could be linked to his CVID phenotype, subsequent reanalysis identified NFKB1 haploinsufficiency as the cause. This study underscores the value of periodic reanalysis of unsolved genetic studies performed with high-throughput technologies (eg, next-generation sequencing and aCGH). This is important because of the ongoing incorporation of new data establishing the relationship between genes and diseases. In the present case, NFKB1 had not been associated with human disease at the time aCGH was performed. Eight years later, reanalysis of the genes included in the chromosome 4 deletion enabled us to identify NFKB1 haploinsufficiency as the genetic cause of our patient’s CVID. In the future, other genes included in the deletion may be linked to human disease, allowing us to better define the molecular basis of our patient’s complex clinical phenotype.